Excitation of Electromagnetic Surface Waves at A Conductor-Plasma Interface by An Electron Beam (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
Electromagnetic surface waves are driven to instability on a conductor plasma interface via Cerenkov and fast cyclotron interaction by an electron beam. A dispersion relation and the growth rate of the instability for this process has been derived. Numerical calculations of the growth rate and unstable mode frequencies have been carried out for the typical parameters of the surface plasma waves. The plasma and beam responses are obtained using fluid treatment and the growth rate is obtained using the first-order perturbation theory. The growth rate increases with the beam density and scales as one-third power of the beam density in Cerenkov interaction and is proportional to the square root of beam density in fast cyclotron interaction. In addition, the real frequency of the unstable wave increases with the beam energy and scales as almost one half power of the beam energy. The effect of the plasma parameters and the strength of the external magnetic field on unstable frequencies and growth rates are analyzed.
Keywords: Surface plasma wave; Electron beam; Instability; Dispersion relation; Growth rate